Expression of Bcl-2 and Bax in Advanced or Metastatic Prostate Carcinoma - Anvari, Kazem; Seilanian Toussi, Mehdi; Kalantari, Mahmoud; Naseri, Shahram; Karimi Shahri, Mahdi; Ahmadnia, Hassan; Katebi, Mehrdad; Sedighi Pashaki, Abdolazim; Dayani, Mahdieh; Broumand, Maryam (Urology Journal, 2012)
Purpose: To evaluate the correlation of Bcl-2 and Bax protein expressions with biochemical failure-free survival in patients with advanced or metastatic prostate carcinoma (PCa) undergoing androgen deprivation therapy. Materials and Methods: This retrospective study was performed on patients with locally advanced (≥ T3) or metastatic PCa, who were referred to Omid Hospital between years 2003 and 2007. All subjects had undergone androgen deprivation therapy. Samples were analyzed immunohistochemically for Bax and Bcl-2 expression. The H-score was calculated for each sample based on intensity and percentage of stained cells. H-score > 50 was considered positive. Results: Thirty-seven patients (13 metastatic and 24 locally advanced) were eligible for analysis. Thirty-six (97.3%) samples were positive for Bax and 26 (70.3%) for Bcl-2 expression. The median H-score for Bax and Bcl-2 was 200 (range, 40 to 300) and 85 (range, 0 to 220), respectively. While there was no correlation between Bax expression and Gleason score, high Bcl-2 expression (H-score > 85) was significantly associated with Gleason score > 7 (P = .004). The median time to progression in the advanced and metastatic groups was 22 (range, 10 to 37) months and 16 (range, 9 to 26) months, respectively. High Bcl-2 expression (P = .01) and prostate-specific antigen > 20 ng/mL (P = .01) were significant predictors of lower biochemical progression-free survival. Conclusion: High Bcl-2 expression was associated with higher Gleason scores and lower biochemical-free survival in patients with advanced PCa undergoing androgen deprivation therapy.